GAMBARAN PENGETAHUAN DAN SIKAP PRIA PRODUKTIF TERHADAP METODE KONTRASEPSI VASEKTOMI DI WILAYAH KERJA PUSKESMAS RAWASARI - Ratna Sari; Nurfitriani Nurfitriani (Universitas Baiturrahim, 2016)
Backround : The high rate of population growth that is not accompanied by an increase in quality of the population, continued management efforts with the family planning program. The majority of Indonesia's population embrace the patriahal culture that reinforces the ego in men who think that family planning program is the responsibility of the wife, and reinforced Data Ministry of Health RI shows community participation in family planning program is still dominated by women than in men, and only a small percentage of men participating become a vasectomy acceptors.Method : This research uses descriptive method with cross sectional approach, which aims to describe the knowledge and attitudes of productive men toward contraceptive method of vasectomy in Community health centers Rawasari year 2015. This study was conducted in Community health centers Rawasari. Population in this study were all Productive men in Community Health Centers Rawasari is 10.912 people and the number of samples in this study were 96 people Sampling technique using purposive sampling techniques, data was collected through questionnaires. Data processing is done by univariate analysis. Result : In this study result, few respondents have a high knowledge of as many as 27 respondents (28.1%). and knowledgeable Low 69 respondents (71.9%). While a positive attitude towards contraception vasectomy as many as 46 respondents (47.9%) and respondents who had a negative attitude of 50 respondents (52.1%). It is necessary for the role of health workers in providing information to couples of childbearing age about the types of contraception.Keywords : Knowledge, Attitude, Contraception Vasectomy